2021
DOI: 10.5688/ajpe848112
|View full text |Cite
|
Sign up to set email alerts
|

Team-based Learning to Promote the Development of Metacognitive Awareness and Monitoring in Pharmacy Students

Abstract: Objective. To evaluate the metacognitive abilities of pharmacy students and determine whether introducing the concept along with team-based learning (TBL) enhances metacognition. Methods. Pharmacy students completed a Metacognitive Awareness Inventory (MAI) and a lowstakes pretest during the first class that evaluated students' knowledge about the therapeutic concepts that would be taught through TBL. The same questions were administered on the comprehensive final examination for the course. For each of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 21 publications
0
20
0
2
Order By: Relevance
“…3 Within pharmacy education, Martirosov and Moser introduced the concept of metacognition and assessed student metacognition before and after a semester-long team-based learning course for second-year student pharmacists at one institution. 15 Their study found that after the course, there was a significant improvement in metacognition, as measured by the 52-item MAI (77% vs. 84%, p<0.01). 15 Their study points to an option to enhance metacognition during the didactic curriculum, but no evaluation was done within experiential education.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…3 Within pharmacy education, Martirosov and Moser introduced the concept of metacognition and assessed student metacognition before and after a semester-long team-based learning course for second-year student pharmacists at one institution. 15 Their study found that after the course, there was a significant improvement in metacognition, as measured by the 52-item MAI (77% vs. 84%, p<0.01). 15 Their study points to an option to enhance metacognition during the didactic curriculum, but no evaluation was done within experiential education.…”
Section: Discussionmentioning
confidence: 94%
“…15 Their study found that after the course, there was a significant improvement in metacognition, as measured by the 52-item MAI (77% vs. 84%, p<0.01). 15 Their study points to an option to enhance metacognition during the didactic curriculum, but no evaluation was done within experiential education. 15 A recent article in experiential education showed the enhanced metacognitive accuracy of student pharmacist self-assessment as compared with faculty assessment of student performance on entrustable professional activities (EPA) between introductory pharmacy practice experiences and the beginning of APPEs; however, there was no overall difference noted in accuracy enhancement throughout the APPE year.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations